An Examination of the Relationship between Mental Distress, Functional and Psychosocial Quality of Life Indicators in a Population Based Sample of Prostate Cancer Survivors Who Received Curative Treatment. Issue 5 (4th September 2020) - Ilie, Gabriela; MacDonald, Morgan; Bell, David; Rendon, Ricardo; Langille, Gavin; Bailly, Gregory; Mason, Ross; Bowes, David; Wilke, Derek; Patil, Nikhilesh; Lawen, Joseph; Grantmyre, John; et al.
Abstract: Introduction: Although survival rates are highest among prostate cancer survivors compared to any other forms of cancer, nearly 60% suffer from mental distress. Here we examine urinary function and psychosocial stressors and their association with poor mental health in a younger group of prostate cancer survivors who have undergone curative treatment. Methods: The study includes 128 men (47 to 70 years old) who received active treatment for prostate cancer, and completed a survivorship online survey between 2017 and 2018. Psychological distress was assessed with Kessler Psychological Distress Scale. International Prostate Symptom Score subscales (incomplete urinary emptying, frequency, intermittency, urgency, weak stream, straining and nocturia) and number of current prostate cancer survivorship stressors were predictors. Multivariate logistic regression was used to fit the model while controlling for months of survivorship since diagnosis, the presence or absence of surgery, radiation or hormone therapy treatment, current medication for depression and demographics. Results: A total of 19.5% of men scored positive for current mental health issues. Prostate cancer survivors who reported increased number of current survivorship stressors (OR 1.48, 95% CI 1.09–2.01), had higher frequency of urination (OR 2.05, 95% CI 1.15–3.64), history of radiation treatment (OR 7.15, 95% CI 1.02–50.35) and were currently on prescribed medication for depression (OR 33.47, 95% CI 3.80–294.87) had higher odds for screening positive for psychological distress compared with their counterparts. Conclusions: These results corroborate recent findings showing an intersection between urological oncology and poor mental health during survivorship, and warrant the development of multidisciplinary teams in addressing survivorship issues in this population.